Market and production of agroecological seeds (Colloquium Agrariae. ISSN: 1809-8215, 2023)
In the last decades, agriculture has been changing mainly in terms of organic production, consumption and market. This increase is due to people's interest in pesticide-free products that meet all environmental, cultural and social issues, presenting themselves as a highly competitive and profitable niche market. For this reason, this bibliographic review aims to describe the market scenario and the production of agroecological seeds, in addition to characterizing the production of organic seeds and evaluating the potential of this market niche that is increasingly the target of investment and food demand.